An infant with cholestasis, acholic stool and high GGT levels - Sağ, Elif; Işık, Güneş; Çebi, Alper Han; Kalyoncu, Mukaddes; Çakır, Murat; Aydoğdu, Sema (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Sağ E, Işık G, Çebi AH, Kalyoncu M, Çakır M, Aydoğdu S. An infant with cholestasis, acholic stool and high GGT levels. Turk J Gastroenterol 2018; 29: 621-2.